Biomarkers of effect: gross and histopathological indicators Atherina boyeri of the Caspian Sea, Kazakhstan Sector (Experimental biology, 2019)
Feature of ichthyofauna North-eastern part of the Caspian Sea is the presence of it includes not only the valuable commercial fish species, but also of low value species who participate in the formation of the food chain. Fish, as the top trophic unit of the aquatic ecosystem, are considered indicators of pollution, therefore pathological studies allow us to estimate and predict effects of finding toxic substances in water. This article presents the results of the morphometric and histological study Caspian Aterina (Atherina boyeri), inhabiting the North-Eastern part of the Caspian Sea. As a result of the study, were found that the biomarkers-effect are pathological changes gill tissue and liver. So, in the gills are observed destructive lamella changes, phenomena of hyperplasia of the primary and secondary gill epithelium and degeneration of cartilage elements. The liver changes manifested in the form of parenchymal hepatocytes dystrophy and vascular reaction. The observed pathological changes gills and liver may affect the survival Atherina boyeri and these organs can serve as biomarkers of effect. Histological study of muscle and gonad it did not reveal any changes pamorphological and observed processes are reversible. In these studies, substantiates use of Caspian Aterina (Atherina boyeri) as a test type of monitoring the water of the Caspian Sea basin and including to predict the number of and quality of harvested species.Key words: Caspian atherina, A. boyeri caspia (Eichwald, 1838), Caspian Sea, histological changes, gills, liver.